Alzheimer’s disease-related presenilins are key to intestinal epithelial cell function and gut immune homoeostasis - Erkert, Lena; Gamez-Belmonte, Reyes; Kabisch, Melanie; Schödel, Lena; Patankar, Jay; Gonzalez Acera, Miguel; Mahapatro, Mousumi; Bao, Lili; Plattner, Christina; Kühl, Anja A.; Shen, Jie; Serneels, Lutgarde; et al. (Gut, 2024)
Objective Mutations in presenilin genes are the major cause of Alzheimer’s disease. However, little is known about their expression and function in the gut. In this study, we identify the presenilins Psen1 and Psen2 as key molecules that maintain intestinal homoeostasis. Design Human inflammatory bowel disease (IBD) and control samples were analysed for Psen1 expression. Newly generated intestinal epithelium-specific Psen1-deficient, Psen2-deficient and inducible Psen1/Psen2 double-deficient mice were used to dissect the functional role of presenilins in intestinal homoeostasis. Results Psen1 expression was regulated in experimental gut inflammation and in patients with IBD. Induced deletion of Psen1 and Psen2 in mice caused rapid weight loss and spontaneous development of intestinal inflammation. Mice exhibited epithelial barrier disruption with bacterial translocation and deregulation of key pathways for nutrient uptake. Wasting disease was independent of gut inflammation and dysbiosis, as depletion of microbiota rescued Psen-deficient animals from spontaneous colitis development but not from weight loss. On a molecular level, intestinal epithelial cells lacking Psen showed impaired Notch signalling and dysregulated epithelial differentiation. Conclusion Overall, our study provides evidence that Psen1 and Psen2 are important guardians of intestinal homoeostasis and future targets for barrier-promoting therapeutic strategies in IBD.
CRIS-Team Scopus Importer:2024-08-30

Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gámez Belmonte, Maria de los Reyes; Gonzalez Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut-vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)-γ is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN-γ-treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN-γ (10 U/mL). After 48 h, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRM™ MS). In total, 1,084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-γ- and control-stimulated HIEC. Several of these proteins were also differentially expressed in various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.
CRIS-Team Scopus Importer:2023-09-08
Keywords: angiocrine; barrier; cytokines; endothelial; IBD-inflammatory bowel disease; interferon; paracrine; secretion

An intravital microscopy-based approach to assess intestinal permeability and epithelial cell shedding performance - Martínez Sánchez, Luz del Carmen; Pradhan, Rashmita; Ngo, Phuong A.; Erkert, Lena; Becker, Lea; Watson, Alastair J.; Atreya, Imke; Neurath, Markus; Lopez Posadas, Rocío (Journal of Visualized Experiments, 2020)
Intravital microscopy of the gut using confocal imaging allows real time observation of epithelial cell shedding and barrier leakage in living animals. Therefore, the intestinal mucosa of anesthetized mice is topically stained with unspecific staining (acriflavine) and a fluorescent tracer (rhodamine-B dextran), mounted on a saline solution-rinsed plate and directly imaged using a confocal microscope. This technique can complement other non-invasive techniques to identify leakage of intestinal permeability, such as transmucosal passage of orally administered tracers. Besides this, the approach presented here allows the direct observation of cell shedding events at real-time. In combination with appropriate fluorescent reporter mice, this approach is suitable for shedding light into cellular and molecular mechanisms controlling intestinal epithelial cell extrusion, as well as to other biological processes. In the last decades, interesting studies using intravital microscopy have contributed to knowledge on endothelial permeability, immune cell gut homing, immune-epithelial communication and invasion of luminal components, among others. Together, the protocol presented here would not only help increase the understanding of mechanisms controlling epithelial cell extrusion, but could also be the basis for the developmental of other approaches to be used as instruments to visualize other highly dynamic cellular process, even in other tissues. Among technical limitations, optical properties of the specific tissue, as well as the selected imaging technology and microscope configuration, would in turn, determine the imaging working distance, and resolution of acquired images.
CRIS-Team Scopus Importer:2020-12-25

Caspase-8 in endothelial cells maintains gut homeostasis and prevents small bowel inflammation in mice - Tisch, Nathalie; Mogler, Carolin; Stojanovic, Ana; Luck, Robert; Korhonen, Emilia A.; Ellerkmann, Alexander; Adler, Heike; Singhal, Mahak; Schermann, Geza; Erkert, Lena; Patankar, Jay; Karakatsani, Andromachi; et al. (Embo Molecular Medicine, 2022)
The gut has a specific vascular barrier that controls trafficking of antigens and microbiota into the bloodstream. However, the molecular mechanisms regulating the maintenance of this vascular barrier remain elusive. Here, we identified Caspase-8 as a pro-survival factor in mature intestinal endothelial cells that is required to actively maintain vascular homeostasis in the small intestine in an organ-specific manner. In particular, we find that deletion of Caspase-8 in endothelial cells results in small intestinal hemorrhages and bowel inflammation, while all other organs remained unaffected. We also show that Caspase-8 seems to be particularly needed in lymphatic endothelial cells to maintain gut homeostasis. Our work demonstrates that endothelial cell dysfunction, leading to the breakdown of the gut-vascular barrier, is an active driver of chronic small intestinal inflammation, highlighting the role of the intestinal vasculature as a safeguard of organ function.
CRIS-Team Scopus Importer:2022-05-13
Keywords: caspase-8; chronic intestinal inflammation; endothelium; necroptosis; vascular homeostasis

Cytokine-Mediated Crosstalk between Immune Cells and Epithelial Cells in the Gut - Mahapatro, Mousumi; Erkert, Lena; Becker, Christoph (Cells, 2021)
Cytokines are small proteins that are secreted by a vast majority of cell types in the gut. They not only establish cell-to-cell interactions and facilitate cellular signaling, but also regulate both innate and adaptive immune responses, thereby playing a central role in genetic, inflammatory, and infectious diseases of the gut. Both, immune cells and gut epithelial cells, play important roles in intestinal disease development. The epithelium is located in between the mucosal immune system and the gut microbiome. It not only establishes an efficient barrier against gut microbes, but it also signals information from the gut lumen and its composition to the immune cell compartment. Communication across the epithelial cell layer also occurs in the other direction. Intestinal epithelial cells respond to immune cell cytokines and their response influences and shapes the microbial community within the gut lumen. Thus, the epithelium should be seen as a translator or a moderator between the microbiota and the mucosal immune system. Proper communication across the epithelium seems to be a key to gut homeostasis. Indeed, current genome-wide association studies for intestinal disorders have identified several disease susceptibility loci, which map cytokine signatures and their related signaling genes. A thorough understanding of this tightly regulated cytokine signaling network is crucial. The main objective of this review was to shed light on how cytokines can orchestrate epithelial functions such as proliferation, cell death, permeability, microbe interaction, and barrier maintenance, thereby safeguarding host health. In addition, cytokine-mediated therapy for inflammation and cancer are discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: cytokines; gut homeostasis; IBD; immunity; inflammation; signaling

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Gámez Belmonte, Maria de los Reyes; Wagner, Yara; Mahapatro, Mousumi; Wang, Ru; Erkert, Lena; Gonzalez Acera, Miguel; Cineus, Roodline; Hainbuch, Saskia; Patankar, Jay; Vöhringer, David; Hegazy, Ahmed N.; Neurath, Markus; et al. (Scientific Reports, 2024)
Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Gasdermin; Gut pathology; Intestinal homeostasis

Know your neighbors: microbial recognition at the intestinal barrier and its implications for gut homeostasis and inflammatory bowel disease - Iyer, Krishna; Erkert, Lena; Becker, Christoph (Frontiers in Cell and Developmental Biology, 2023)
Intestinal epithelial cells (IECs) perform several physiological and metabolic functions at the epithelial barrier. IECs also play an important role in defining the overall immune functions at the mucosal region. Pattern recognition receptors (PRRs) on the cell surface and in other cellular compartments enable them to sense the presence of microbes and microbial products in the intestinal lumen. IECs are thus at the crossroads of mediating a bidirectional interaction between the microbial population and the immune cells present at the intestinal mucosa. This communication between the microbial population, the IECs and the underlying immune cells has a profound impact on the overall health of the host. In this review, we focus on the various PRRs present in different cellular compartments of IECs and discuss the recent developments in the understanding of their role in microbial recognition. Microbial recognition and signaling at the epithelial barrier have implications in the maintenance of intestinal homeostasis, epithelial barrier function, maintenance of commensals, and the overall tolerogenic function of PRRs in the gut mucosa. We also highlight the role of an aberrant microbial sensing at the epithelial barrier in the pathogenesis of inflammatory bowel disease (IBD) and the development of colorectal cancer.
CRIS-Team Scopus Importer:2023-10-20
Keywords: inflammatory bowel disease (IBD); intestinal epithelial cells (IECs); intestinal homeostasis; microbiome; mucosal immunity; pattern recognition receptors (PRRs)

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

The Regulation of Intestinal Inflammation and Cancer Development by Type 2 Immune Responses - Gamez-Belmonte, Reyes; Erkert, Lena; Wirtz, Stefan; Becker, Christoph (International Journal of Molecular Sciences, 2020)
The gut is among the most complex organs of the human body. It has to exert several functions including food and water absorption while setting up an efficient barrier to the outside world. Dysfunction of the gut can be life-threatening. Diseases of the gastrointestinal tract such as inflammatory bowel disease, infections, or colorectal cancer, therefore, pose substantial challenges to clinical care. The intestinal epithelium plays an important role in intestinal disease development. It not only establishes an important barrier against the gut lumen but also constantly signals information about the gut lumen and its composition to immune cells in the bowel wall. Such signaling across the epithelial barrier also occurs in the other direction. Intestinal epithelial cells respond to cytokines and other mediators of immune cells in the lamina propria and shape the microbial community within the gut by producing various antimicrobial peptides. Thus, the epithelium can be considered as an interpreter between the microbiota and the mucosal immune system, safeguarding and moderating communication to the benefit of the host. Type 2 immune responses play important roles in immune-epithelial communication. They contribute to gut tissue homeostasis and protect the host against infections with helminths. However, they are also involved in pathogenic pathways in inflammatory bowel disease and colorectal cancer. The current review provides an overview of current concepts regarding type 2 immune responses in intestinal physiology and pathophysiology.
CRIS-Team WoS Importer:2021-01-15